(Z)-4-(Azulen-1-ylmethylene)-2-phenyloxazol-5(4H)-one - Mihaela Cristea; Alexandru C. Razus; Sergiu Shova; Marcel-Mirel Popa; Mihai Răducă; Florea Dumitrascu (Molbank, 2025)
The title compound, i.e., (Z)-4-(azulen-1-ylmethylene)-2-phenyloxazol-5(4H)-one (3), has previously been synthesized in a good yield (56%) using the Erlenmeyer–Plöchl procedure. The crystal structure of 3 is described herein along with the results of a Hirshfeld surface analysis. Crystals of compound 3 were obtained through the slow evaporation of a mixture of petroleum ether/dichloromethane = 1:1 (vol.) at room temperature. This compound has a monoclinic system: a P21/n space group at room temperature. Its crystal packing is driven by π-π interactions between neighboring molecules in the range of 3.60–3.71 Å and by hydrogen bonds (D-H···A = 2.58 Å).